Uranium(IV) Complexes with O-and N-Donor Ligands - Sharma, Ramadhar; Sharma, S.N.; Kumar, Pravin; Ranjan, Rajeev; Choudhary, S.N. (Asian Journal of Chemistry, 2012)
New complexes of U(IV) with O and N-donor Ligands are reported. The ligands (TH), variedly substituted monobasic bidentate triazene-1-oxides, have been used. UCl4 and TH were refluxed in ethanolic medium in varied rations. The complexes obtained were invariably in 1:4 molar ratio. The complexes were characterized by elemental analysis, conductance measurements in nitromethene, magnetic moment values were obtained at room temperature, IR in the range 200-400 cm-1 in KBr discs and electronic spectral studied. U(IV) was found to possess the coordination number eight.